Memahami Pesan Dakwah dalam Siaran - Erwan Effendi; Azwar Surya Syahputra; Luthfi Ramadhan; Rika Malia Panjaitan; Radja Abdul Kadir Nasution (Departement of Mathematics Education, 2023)
Managing broadcasting television is not the same as managing companies in general. Moreover if there is a da’wah mission. Management concepts are not necessarily applicable in broadcasting management. Integrating it means balancing the interests of the media owner and the public as the audience as well as the owner of the rights to the frequency managed by the broadcast media. While broadcasting media must continue to function as a means of entertainment, information, public services and economic functions. Broadcasting media management places more emphasis on planning, which include positioning, segmentation, targeting, formatting and programming. The rest, broadcasting management concepts are almost the same as management in general. In the end, concepts in the political economy of the media remain decisive in winning audience choice, including the broadcasting media which carrying da’wah mission. These concepts include: commodification, spatialization and structuration.